Student Perspective: Religious Character Values in Upin and Ipin Animated Cartoons - Saputra, Daffa Untara; Sanusi, Anwar; Rahman, K.A. (MKWK PAI Universitas Jambi, 2024)
This study aims to determine students’ perspectives on character values in Upin and Ipin animated cartoons. This type of research uses qualitative methods with descriptive methods. Islamic character values are something that all Muslims must have. To form individual characteristics that foster honesty, always maintain their relationship to Allah SWT, always respect parents and respect others, character education media is needed. Cartoons or animations are not just entertainment but can be an educational medium for Islamic character values in an individual. The results showed that Islamic character values in Upin and Ipin cartoons or animations based on student perspectives in the episode “Spesial menyambut Ramadhan” have the following character values: Faith, Mutual Respect, Tolerance, and Mutual Respect, from these four character values can be concluded that these four values are the most dominant religious character values in Upin and Ipin animated cartoons in the episode “Spesial menyambut Ramadhan”.